JOHN CALVIN: GERAKAN, PEMIKIRAN DAN WARISANNYA DALAM SEJARAH GEREJA MENURUT TELAAH LITERATUR - Marde Christian Stenly Mawikere; Sudiria Hura (Program Studi Teologi, Fakultas Teologi, Institut Agama Kristen Negeri Manado, 2023)
This article describes John Calvin, the second generation of reformers in church history or Christian history who systematized reform theology through his theological movements and thoughts. This description is based on randomly selected literature reviews that study the life of John Calvin and his theological thoughts that focus on the sovereignty of the Triune God over all His creation. The specialty of Calvin's thought also lies in the integrity and integration between abstract theology and holistic spirituality. Therein lies the strength of the church which must continue to be reformed, namely the supremacy of God's sovereignty and integrative theology-spirituality which is the legacy of John Calvin which should be actualized and continuous in the procession of the church in its historical course.